Implementasi Kebijakan Ruang Terbuka Hijau (Rth) Dalam Tata Kelola Ruang Di Kota Palu - Wardana, Kelvin Gosal Thendy; Rivai, Abdul; Firmansyah, Andi Maman (JPS: Journal of Publicness Studies, 2024)
Green Open Space (RTH) is one of the important elements in urban development that functions to improve the quality of the environment and urban life. This study aims to analyze the role of RTH in supporting the balance of urban ecosystems and to evaluate the adequacy and distribution of RTH in spatial governance in Palu City. The methods used in this study are a qualitative approach with the purposive sampling method and Snowball Sampling with a total of 3 informants. The data used consisted of secondary data obtained from the Palu City Environmental Agency, as well as primary data obtained through direct observation and direct interviews with informants. Data analysis is carried out by data collection, data condensation, data display and conclusion drawing/verification. The results of the study show that Palu City has an RTH area that is still below the standards set by laws and regulations, which is at least 30% of the total city area. The uneven distribution of RTH between the downtown areas is due to the lack of perspective from OPD, lack of resources, and minimal community involvement in the implementation of this policy. This research also identifies potential areas that can be developed into new RTH to improve environmental quality and residents' welfare. Therefore, this study suggests the need for more effective policies in the management and planning of green open spaces in the future as well as the involvement of the role of the community that must be maximized.